Democracy and governance: Does electoral system matter? - Joseph, T.M. (2007)
The present article looks into the unrepresentative character of the existing `first-past-the-post' (FPTP) system in India and suggests certain alternative models so that our country can be better governed. The FPTP system of election results in the victory of a candidate with a minority (less than fifty per cent of votes polled) of votes which enables the candidate who gets the most votes (need not be a majority of total votes polled) to win an election in a multi-cornered contest. This implies that only a minority of voters who have voted for the victorious candidate get any representation at all. The voters (often a majority) who voted for the defeated candidates go unrepresented. It means that they have wasted their votes. At the national level, this phenomenon leads to a disproportion between the percentage of votes polled by political parties and the number of seats won by parties. In order to correct this drawback in the present Indian system, alternative models of electoral systems are analysed and the Mixed Member Proportional system is suggested in the article. - Reproduced.
Keywords: Electoral systems - India; India - Politics and government; Democracy - India; Democracy